Ageing Cattle: The Use of Radiographic Examinations on Cattle Metapodials from Eketorp Ringfort on the Island of Öland in Sweden - Telldahl, Ylva (PLoS One, 2015)
In this paper conventional X-ray analysis of cattle metapodials is used to study the age structure of slaughtered cattle at Eketorp ringfort on the island of Öland, Sweden. The X-ray analyses suggest that several animals in both phases were slaughtered aged 4–8 years. More oxen/bulls than cows reached the advanced age of over 8 years, yet in phase III more oxen/bulls seem to have been slaughtered between the ages of 2 and 8 years. These differences may reflect a change in demand for meat related to the character of the site. The results also show a correlation between metapodials with a pathology connected to biomechanical stress and older animals. This suggests that male cattle were used both in meat production and as draught animals. Asymmetry in male metatarsals such as distal broadening of the lateral part of the medial trochlea was visible on the X-ray images. The bone element also indicates a denser outer cortex of the medial diaphysis in comparison to the inner medulla. This could be the result of repetitive mechanical stress. Two metatarsals from cows were documented with distal asymmetry indicating that cows were also used as working animals. Bone elements with changes in the articular surfaces were more common in metapodials from cows with an X-ray age of over 3–4 years. These results highlighted the slaughter age difference between oxen/bulls and cows, enabling a better understanding of animal husbandry and the selection of draught cattle at Eketorp ringfort.